Introductory lecture: recent research progress on aggregation-induced emission. (30th November 2016) - Wang, Yuancheng; Zhang, Guanxin; Gao, Meng; Cai, Yuanjing; Zhan, Chi; Zhao, Zujin; Zhang, Deqing; Tang, Ben Zhong
Abstract : Since the discovery of the aggregation-induced emission (AIE) phenomenon in 2001, research on AIE molecules has drawn much attention, and this area has been expanding tremendously. This brief review will focus on recent advances in the science and application of AIE molecules, including new mechanistic understanding, new AIE molecules for sensing and imaging, stimuli-responsive AIE molecules and applications of AIE molecules for OLEDs. Moreover, this review will give a perspective on the possible opportunities and challenges that exist in the future for this area.